Periódicos científicos nas mídias digitais : práticas inovadoras para a comunicação pública da ciência - Miranda, Téo de (2024)
This doctoral research conducts a study on Brazilian scientific journals which work in digital version, including management, availability and broadcasting of content entirely online. The research is mainly based on the universe of humanities, focused on the field of Communication and information. The main objective was to identify, describe and analyse scientific dissemination initiatives through social media websites, done by three scientific journals of open access, which dialogue with the field of Communication and information, evaluated by the Coordination of Superior Level Staff Improvement (Capes in Portuguese) between Qualis A1 and A2 that make their contents available in Portuguese. The analytical or analysis were based on theorists such as Canevacci, Castells, Fleck and Weiss, among other references brought in to produce intelligibility to the obtained data. Methodologically, the selection of the three magazines was carried out through applying filters, resulting in the magazines of Human Science and Applied Social Science and Health Science, they are the following: Data Magazine (Revista Dados), linked to the Institute of Social and Political Studies (IESP) from the State of Rio de Janeiro University (UERJ); Anthropology Magazine (Revista de Antropologia), from the Faculty of Philosophy, Letters and Human Sciences of the University of São Paulo (FFLCH/USP); History, Science, Health Magazine (Revista História, Ciências, Saúde) – from Manguinhos -, linked to the Osvaldo Cruz House (Casa de Oswaldo Cruz). More than analysing each of their websites, searches were carried out on their activities on social media networks: Facebook, Instagram and Twitter (X). The results obtained from the unfolding of the analysis show that in analytic incursions, some aspects intersect: visual communication and social interactions through the medias that were used. Such practices have benefited the scientific communication, facilitated the process of editing and the delivering to the academic public. It was noted that part of the journals tried to promote the communication of science beyond the academic public, acting in an innovative way by using social medias, incorporating multimedia strategies and practices.